Synthesis and characterization of a pressure-sensitive adhesive based on an isobutyl acrylate / 2-ethylhexyl acrylate copolymer (2004)
ABSTRACT: A removable pressure-sensitive adhesive was obtained by free-radical emulsion polymerization. The product is a low-viscosity copolymer from different polar and apolar acrylic monomers consisting of microspheres of about 1 µm diameter. 2-Ethylhexyl acrylate and isobutyl acrylate were used as non-polar constituents while acrylic acid and acrylamide provided the more polar constituents to regulate the cohesive force of the adhesive. The amounts of initiator, water and emulsifier (nonylphenol) were varied to obtain the best adhesive properties at the given copolymer composition. The resulting adhesive showed the desired balance of low tack and good adhesive strength in combination with a wide variety of substrates, which made it useful as a removable adhesive for many applications. The product was characterised by viscometry, measurements of tack and peel strength, FTIR, DSC, and microscopy.